Determinants of Socially Oriented State Policy of Economic Relations Development - Петруненко, Ярослав Вікторович; Петруненко, Я. В.; Петруненко, Ярослав Викторович; Petrunenko, Yaroslav V.; Petrunenko, Iaroslav V.; Подцерковний, Олег Петрович; Подцерковний, О. П.; Подцерковный, Олег Петрович; Podtserkovnyi, Oleh P.; Podtserkovnyi, Oleg P.; Кулініч, Ольга Олексіївна; Кулініч, О. О.; et al. (ASERS Publishing, 2020)
At the present stage of development of economic systems, a multitude of countries around the world are focused on implementing such a regulatory policy of the state that would enable sustainable development and formation of a socially oriented type of market economy, where the main goal is to ensure the welfare and high living standards of the population. Thus, the purpose of the research in this article is to identify the determinants of socially oriented state policy for the development of economic relations, respectively, the subject is to determine the strategic priorities of such policy. To achieve this purpose, the article employs general theoretical and special legal methods of research, in particular, the dialectical method of scientific cognition allowed to trace the current trends in the development of national policy, the comparative legal method allowed to perform a comparative analysis of strategic priorities of national policy in foreign countries, which reached a significant level of socio-economic development, analytical method applied in formulating generalized and elaborate conclusions based on the research findings. Based on the results of the study, the authors came to the conclusion that the modern socially oriented state regulatory policy is based on the current form of state government, which determines the political regime of the country and the legislative basis for regulating the economic relations of economic entities, which operate in accordance with the formed institutional environment in the country.

На сучасному етапі розвитку економічних систем безліч країн світу орієнтована на реалізацію такої регуляторної політики держави, яка б забезпечила стійкий розвиток і формування соціально орієнтованого типу ринкової економіки, де основною метою є забезпечити добробут і високий рівень життя населення. Таким чином, метою дослідження в цій статті є виявлення детермінант соціально орієнтованої державної політики розвитку економічних відносин, відповідно, предметом є визначення стратегічних пріоритетів такої політики. Для досягнення цієї мети в статті використовуються загальнотеоретичні та спеціально-правові методи дослідження, зокрема, діалектичний метод наукового пізнання дозволив простежити сучасні тенденції розвитку національної політики, порівняльно-правовий метод дозволив провести порівняльний аналіз стратегічних пріоритетів національної політики в зарубіжних країнах, які досягли значного рівня соціально-економічного розвитку, аналітичний метод, що застосовується при формулюванні узагальнених та детальних висновків на основі результатів дослідження. На підставі результатів дослідження автори дійшли висновку, що сучасна соціально орієнтована державна регуляторна політика базується на сучасній формі державного правління, що визначає політичний режим країни та законодавчу базу регулювання економічних відносин між економічними суб’єктами, які діють відповідно до сформованого в країні інституційного середовища.

На современном этапе развития экономических систем множество стран мира ориентированы на реализацию такой регуляторной политики государства, которая бы обеспечила устойчивое развитие и формирование социально ориентированного типа рыночной экономики, где основной целью является обеспечить благополучие и высокий уровень жизни населения. Таким образом, целью исследования в этой статье является выявление детерминант социально ориентированной государственной политики развития экономических отношений, соответственно, предметом является определение стратегических приоритетов такой политики. Для достижения этой цели в статье используются общетеоретические и специально-правовые методы исследования, в частности, диалектический метод научного познания позволил проследить современные тенденции развития национальной политики, сравнительно-правовой метод позволил провести сравнительный анализ стратегических приоритетов национальной политики в зарубежных странах, достигших значительного уровня социально экономического развития, аналитический метод, который применяется при формулировке обобщенных и детальных выводов на основе результатов исследования. На основании результатов исследования авторы пришли к выводу, что современная социально ориентированная государственная регуляторная политика базируется на современной форме государственного правления, определяет политический режим страны и законодательную базу регулирования экономических отношений между экономическими субъектами, действующими в соответствии с сформированной в стране институциональной среды.
Petrunenko I. V. Determinants of Socially Oriented State Policy of Economic Relations Development / I. V. Petrunenko, O. P. Podtserkovnyi, O. O. Kulinich // Journal of Advanced Research in Law and Economics. – V. 10 (6). – ASERS Publishing, 2020. – P. 1732-1740.